Hydrops fetalis in a preterm newborn heterozygous for the c.4A>G SHOC2 mutation. Issue 4 (23rd January 2014) - Gargano, Giancarlo; Guidotti, Isotta; Balestri, Eleonora; Vagnarelli, Federica; Rosato, Simonetta; Comitini, Giuseppina; Wischmeijer, Anita; La Sala, Giovanni Battista; Iughetti, Lorenzo; Cordeddu, Viviana; Rossi, Cesare; Tartaglia, Marco; et al.
<x xml:space="preserve">Abstract</x> Fetal hydrops is a condition resulting from interstitial fluid accumulation in fetal compartments secondary to increased capillary permeability and characterized by high rates of perinatal mortality and morbidity. Clinical features include skin edema, hydrothorax, pericardial effusion, ascites with or without polyhydramnios, and placental edema. While it may occur as associated feature in multiple disorders, it has been documented to recur in Noonan syndrome, the most common disorder among RASopathies, but also in cardiofaciocutaneous and Costello syndromes. Here, we report on the occurrence of severe hydrops in a newborn heterozygous for the invariant c.4A>G missense change in SHOC2 which underlies Noonan‐like syndrome with loose anagen hair, documenting that it represents a clinically relevant complication in this condition, shared by RASopathies. © 2014 Wiley Periodicals, Inc.